Fishery Socioeconomic Outcomes Tool: A rapid assessment tool for evaluating socioeconomic performance of fisheries management. (July 2019) - Smith, Sarah L.; Karasik, Rachel; Stavrinaky, Aristoteles; Uchida, Hirotsugu; Burden, Merrick
Abstract: As linked social-ecological systems, evaluating the socioeconomic outcomes of fisheries management is essential to understanding fishery performance. While a number of tools have been developed in recent years to evaluate social and economic outcomes of fisheries, many require extensive data collection, making them difficult to implement on a large scale, while others rely on existing data, limiting their applicability to data-limited fisheries. Additionally, socioeconomic objectives of fisheries are likely to differ substantially between fisheries of different scales operating in different geographic and socio-cultural contexts, making the development of universal indicators and comparing results between fisheries challenging. This paper describes a novel tool for evaluating and tracking fishery management socioeconomic outcomes by linking outcomes directly to management objectives. Indicators of these outcomes are scored by key informants and weighted according to the importance of particular fishery management objectives, resulting in standardized scores of fishery management outcomes. The resulting scores can be compared between fisheries and tracked over time. This tool was tested in two disparate fisheries on the U.S. West Coast and in Sinaloa, Mexico. Results of testing demonstrate that the outcomes generated similar scores, although the primary objectives of each were very different, permitting comparison of the performance of the two fisheries. The results for the West Coast groundfish fishery were groundtruthed using existing data to assess reliability of survey scores. This tool furthers the landscape of fishery evaluation by enabling comparison of performance among dissimilar fisheries and by facilitating the rapid assessment of social outcomes of fisheries management. Highlights: Describes a new tool for evaluating socioeconomic outcomes of fisheries management. Varied fishery types and objectives make social outcomes challenging to evaluate. New tool evaluates fisheries outcomes linking them to socioeconomic objectives. Standardized performance indices allow for comparison across diverse fisheries. Groundtruthing results with existing data found tool yielded accurate results.